2008
DOI: 10.1037/1938-8926.1.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Who's in, who's out: Examining race, gender and the cohort community.

Abstract: Many teacher education programs have adopted a cohort structure which offers attractive administrative and organizational benefits while promoting classroom community. This study examines one urban teacher preparation program that employed a cohort model. Using focus groups and survey data, this mixed methods study compared results on the basis of race and gender. Findings suggest that while the cohort structure created a strong classroom community among the majority of students, specific minority populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…Each cohort took the initiative to set up its own Facebook group that was limited only to cohort members, and survey results show this was a primary source of interaction and a way to reduce feelings of isolation. Previous research has demonstrated the potential for a cohort structure to result in the social exclusion of individuals who do not fit within the demographic or ideological makeup of the group (Agnew et al, 2008;Rovai & Ponton, 2005;Seifert, 2010), but results of this survey do not suggest that cohort members excluded others from their group communication. It is important to note that the formation of Facebook groups became a cohort tradition of sorts.…”
Section: Discussioncontrasting
confidence: 66%
“…Each cohort took the initiative to set up its own Facebook group that was limited only to cohort members, and survey results show this was a primary source of interaction and a way to reduce feelings of isolation. Previous research has demonstrated the potential for a cohort structure to result in the social exclusion of individuals who do not fit within the demographic or ideological makeup of the group (Agnew et al, 2008;Rovai & Ponton, 2005;Seifert, 2010), but results of this survey do not suggest that cohort members excluded others from their group communication. It is important to note that the formation of Facebook groups became a cohort tradition of sorts.…”
Section: Discussioncontrasting
confidence: 66%
“…Our results confirmed that female students paid more attention and felt more confident than their male peers in these kinds of learning arrangements. Other researchers found similar results who posed that female students experienced greater satisfaction in a novel computersupported environment (González-Gómez et al, 2012) and were more inclined to work with each other in a community atmosphere (Agnew et al, 2008). Moreover, female students' demonstrated similar attitudes either learning in collaborative and traditional environments when they were single-gender grouped in the e-learning modality.…”
Section: Attitude and Achievement Towards Biology Based On Students' ...supporting
confidence: 58%
“…Our study contrasted the findings of previous research. In their study, Agnew et al (2008) found that students were more likely to remain silent as faculty attempted to engage their students in race-related conversations. However, our participants of color readily vocalized their recognition of racial stereotypes in the film, their encounters with prejudice on campus, and a willingness to help their peers build cultural competence.…”
Section: Discussionmentioning
confidence: 98%
“…However, conversations about race and ethnicity integrated into the college classroom may not always be fruitful. For example, Agnew, Mertzman, Longwell-Grice, and Saffold (2008) found that students of color—although members of a cohort—felt that being open and honest in discussing issues of race and gender put them at risk. Agnew et al pointed to a specific example of a Hmong student who remained silent as the cohort discussed the Hmong community.…”
Section: Review Of Literaturementioning
confidence: 99%